TINGKAT KESESUAIAN LINGKUNGAN PERMUKIMAN PASCA RELOKASI DENGAN STANDAR PERMUKIMAN LAYAK HUNI STUDI KASUS PERMUKIMAN DI KELURAHAN MOJOSONGO, SURAKARTA - Aulia Rasma Indah; Winny Astuti; Galing Yudana (ARSITEKTURA, 2016)
Surakarta City has some problems of settlement, one of which is illegal settlement in the river bank. One of government’s programs to deal with it is relocation program. One of beneficiaries of the program is Kelurahan Sewu residence which was relocated to Kelurahan Mojosongo residence. The objective of settlement relocation is to make the people get appropriate house and environment free of flood disaster usually encountered by them annually. The parameter used to evaluate the aspects in this research was based on the standard for appropriate settlement environment. This study was conducted to find out the compatibility of standard appropriate settlement environment application to post-relocation settlement based on the existing condition and public opinion. A descriptive comparative analysis was conducted to find out the extent to which standard appropriate settlement was applied. The study found that relocation settlement environment condition based on the result of observation and public opinion get total scoring of 2.763. From the scoring obtained, it could be seen that data of field condition and public opinion indicated that post-relocation settlement in Kelurahan Mojosongo from Kelurahan Sewu had met category “appropriate/suitable” to standard appropriate settlement. This explanation suggested that relocation conducted from river bank settlement in Kelurahan Sewu to Kelurahan Mojosongo helped the people meet their need for settlement with appropriate condition. People could get better life compared with that in previous location before receiving relocation.